PRODUKTIVITAS TENAGA KERJA PEKERJAAN PELAT LANTAI PADA PROYEK PEMBANGUNAN GEDUNG RUMAH SAKIT IBU DAN ANAK NIRMALA KEDIRI - Putri, Tiara Maulinda (Jurnal Vokasi Teknik Sipil, 2023)
Building construction performance requires a work system determined by the performance of its workers, namely the level of effectiveness of workers completing their work and many methods that can be used to measure worker productivity. The objective of this research is to identify and analyze the level of activity of workers' productivity by using the methodwork sampling at the Mother and Child Hospital Nirmala Kediri. The purpose of this study was to determine labor productivity in floor slab work on the Nirmala Kediri Mother and Child Hospital Building project. 1 of 2022, and the factors that affect labor productivity in floor slab work. Case research and field research study intensively, in detail, and in depth on the background and current situation. Worker productivity in the construction of the Mother and Child Hospital building Nirmala Kediri per floor with a working floor of 56,023 m2/day, 1st floor of 24,049 m2/day, 2nd floor with a yield of 21,043 m2/day, and roof floor with a yield of 17,595 m2/day. According to the field coefficient value that has been set in PUPR No. 1 of 2022 on the work of floor slabs the comparative value of the field coefficient is smaller. Factors that affect labor productivity in the floor slab work are bad weather conditions, delays in materials, lack of control and monitoring, lack of skill in the workforce, and the condition of the field area that is not large.